Innovative Functional Fruit Leather from Bidara Fruit and Citrus Peel with Carrageenan for Sustainable Food Processing - Caroline Noel Amaris Purnomo; Karyn Gracia Hartono; Karla Katina Salim Nohkarsan (JFCN: Journal of Food, Culinary, and Nutrition, 2025)
Concerns  about  food  waste  and  the  need  for  sustainable  functional  food  has  been  growing  and therefore  led  to  the  search  for  fruit  based  functional  snacks  that  are  formulated  with  natural ingredients and also low environmental impact. This review aims to search for the potential of the use of bidara fruit (Ziziphus mauritiana), arabic gum, citrus peel, and carrageenan as a functional fruit leather. Thus, this review fills the gap by integrating underutilized local fruits (bidara) and food industry by-products (citrus peel) with natural hydrocolloids (carrageenan) into a sustainable and functional snack formulation. Literature with year limitations from the last five years was analyzed using databases such as Google Scholar and PubMed with keywords searched such as "fruit leather," "bidara fruit," "citrus peel," "carrageenan," and "functional food”. Bidara fruit, the main ingredient of this fruit leather, is a tropical fruit with high levels of vitamin C, flavonoids and phenolics which makes  it  has  antioxidant  potentials.  Citrus  peel  that  usually is  discarded  as  food  waste,  is  a  rich natural source of pectin that enhances gelling properties of the product and also a valuable source of  polyphenol,  therefore  adding  functional  benefits  and  contributing  to  sustainability  through upcycling. Carrageenan addition enhances the structure by forming stable hydrogen bonds between polysaccharides  and  fruit  pectins,  improving  texture  and  preventing  syneresis.  The  ingredients listed  were  blended  into  a  puree  form  and  then  dried  at  low  temperature  in  order  to  preserve bioactive compounds. The resulting fruit leather exhibits a flexible-chewy texture, appealing sensory characteristics,  and  retained  significant  bioactive  content,  including  vitamin  C  and  phenolic compounds. This review demonstrates that the combination of bidara, citrus peel, and carrageenan can  produce  a  nutrient-rich,  sustainable  fruit  leather  suitable  as  a  healthy  functional  snack.  This product aligns with sustainable development goals (SDGs) by reducing food waste and utilizing local natural resources efficiently.